AL-AZHAR DALAM MEMODERNISASI PENDIDIKAN ISLAM - Hartono Hartono (Universitas Muhammadiyah Tangerang, 2020)
This study examines the efforts of Al Azhar in modernizing Islamic education in the efforts of superior school. The conclusion of the study is the existence of modernization of Islamic education in Al Azhar school which has been around since its exist, namely by emphasizing the quality of Islamic education at that time, besides no one has quality Islamic education which integrates science and religion to achieve the superior value.